In vitro polyoma DNA synthesis: requirement for cytoplasmic factors. - Francke, B (1975)
Purified nuclei from polyoma-infected mouse (3T3) cells were found to be greatly reduced in their ability to synthesize viral DNA in vitro when compared with a crude system consisting of an unfractionated hypotonic lysate of the infected cells. The synthetic capacity of the nuclei could be fully reconstituted when a high-speed cytoplasmic supernatant was added back to them. Cytosols from uninfected mouse, monkey, and hamster cells were equally as effective in stimulating purified nuclei as that of virus-infected mouse cells. Optimal complementation required high concentrations of the cytosol, and most of the complementing activity was destroyed by heating to 60 C. Dialysis had no effect on the activity. Analysis of the viral DNA synthesized in purified nuclei showed an accumulation of Okazaki-type short DNA chains, which could be chased into viral progeny DNA strands if cytosol was added back to the nuclei. Kinetic analysis of the pulse-labeling pattern of viral replicative DNA showed a strong dependence of the extension of viral progeny strands and of the processing of Okazaki-type fragments on the amount of cytosol present during the reaction. It is suggested that the cytoplasmic DNA polymerase might be one of the active components in the cytosol, but most likely not the only one.